(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The study aims to determine how the creativity methodology can be used in process design to achieve a competitive advantage. This methodology was applied to the toothpaste product, which was proposed to be produced by the Al-Mamoun factory of the General Company for Food Products. Actual data were collected from the factory’s records and reports for the years 2018 and 2019. The study concluded that it is necessary to measure creativity quantitatively to determine its contributions to the process design, and then to achieve the competitive advantage. The study also concluded that the clove-flavored toothpaste product lacked a competitive advantage due to the lack of application of the creativity methodology used to the process design, which made the product uncompetitive in the marketplace. The idea was canceled and the actual production was not started. As a result, the study recommended the necessity of using the creativity methodology, as proposed in this study, in presenting ideas for new products in Al-Mamoun factory. The study also recommended that the process should designed by collecting financial and non-financial data to ensure the proper use of these data to improve the process performance indicators and improving the competitive advantage of this product.